Foreign policy as provocation - Maihold, Günther (Stiftung Wissenschaft und Politik, 2009)
Many of Venezuelan President Hugo Chávez's appearances on the world stage can rightly be called provocations. His verbal radicalism and regular threats to cease supplying oil to the United States make international headlines. But his rhetorical gestures cannot be dismissed as the megalomania of a
Keywords: Forschungsbericht; Außenpolitik; Ursache; Ziel; Innenpolitik; Politisches System; Einflussgröße; Circumstantia; Kultur; Ideologie; Süd-Süd-Beziehungen; Wirtschaftsbeziehungen; Rohstoffreserve; Erdölpolitik; Diplomatie; Public Diplomacy; Venezuela